Physical Stability and Antioxidant Activity of Pee-Off Gel Mask Ethanol Extract of Buas-buas Leaf (Premna serratifolia L.) - Weni Puspita; Heny Puspasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
This study aims to determine the physical stability and antioxidant activity of peel-off gel mask ethanol extract of buas-buas leaf (Premna serratifolia L.). The ethanol extract of buas-buas leaves was obtained by maceration using 70% ethanol solvent, then concentrated using a rotary evaporator to get a thick extract. Formulation EEDB into a peel-off gel mask with a concentration of each EEDB (FI: 1%, FII: 2%, FIII : 3%). The EEDB peel-off gel mask formula was tested for physical stability by cycling test method using a climatic chamber at a temperature of 40°C ± 2°C and 4°C ± 2°C for six cycles. The tests included organoleptic, homogeneity, viscosity, pH, spreadability, and drying time. An antioxidant test was carried out using the DPPH method. The results of the physical stability test on the three EEDB peel-off gel mask formulas (FI: 1%, FII: 2%, FIII: 3%) showed good physical stability because there was no significant difference during six storage cycles (P>0.05) with the results of the preparation have a characteristic aroma of oleum citri, brownish-green in color, have a thick, homogeneous texture, meet the requirements of pH, viscosity, spreadability, and drying time. The stability test results of the antioxidant activity of the peel-off gel mask EEDB in the three formulas showed no significant change (P>0.05). The antioxidant activity during six storage cycles with the highest average percent inhibition before and after the cycling test, namely in Formula III, was 77.20 ± 0.28%.